Papers - Theoretical Studies - Effect of Impregnating Waters on Electrical Conductivity of Soils and Rocks - Karl Sundberg (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
ElectRical investigations carried out in regions containing sedimentary rocks showed that sediments generally are good electrical conductors, a fact which at the present time is used for structural investigations by electrical methods. It is of fundamental importance, not only for these investigations but also for electrical prospecting in general, to know the electrical properties of various soils and rocks. It will be useful, therefore, to discuss this question with the hope that the general points of view discussed in this paper will perhaps be completed by further observations and determinations of material from various localities. This paper is based principally on the study of literature, and the purpose is primarily a discussion of the main factors that determine the electrical conductivity of soils and rocks. It will follow, however, that the factors discussed here also frequently decide how far a certain orebody can be regarded as a good electrical conductor compared with the surrounding rocks. All rocks are more or less porous, and the pores are filled with liquids and gases. Their electrical conductivity, therefore, depends on the following factors: 1. The electrical conductivity of minerals composing the rock. 2. Electrical conductivity of the liquid filling the pores. 3. Proportion of the volume of liquid filling pores of the rocks to the solid rock material. 4. Shape of the pores. 5. Arrangement of the particles of gas and liquids. 6. Temperature. Dry minerals, with the exception of certain ore minerals, are complete nonconductors from the point of view of applied geophysics; in the present investigation we deal with rocks which have no conducting minerals, and factor 1, therefore, is not important. The same is true of soils. The liquids contained in soils and rocks in most cases are waters, sometimes oil. As oil is a nonconductor of electricity, the impregnating waters will determine the electrical conductivity of soils and rocks.